2003
DOI: 10.1086/379838
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Surrogate Markers for Protection againstPlasmodium falciparumInfection and Clinical Malaria Identified in a Senegalese Community after Radical Drug Cure

Abstract: Plasmodium falciparum expresses many antigens, which elicit various immune responses in exposed individuals, but no simple surrogate marker for protection has yet been developed. In this prospective survey, we looked for immune responses predictive of protection at various stages of progression from parasite inoculation to onset of disease. We studied 110 Senegalese volunteers from an area in which malaria is mesoendemic after they had received eradication therapy. We evaluated 4 protection-related outcomes (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 48 publications
5
51
1
Order By: Relevance
“…MSP1p19 antigen used in this study [18] is strongly recognized by the sera of infected individuals, and IgG responses were shown to be significantly associated with delayed infection following drug cure [19], and with clinical protection [20]. Our data show that, in both study groups, patients with cerebral malaria had significantly lower levels of anti-GPI antibodies compared to individuals with mild or asymptomatic malaria.…”
Section: Differential Antibody Responses To P Falciparum Glycosylphomentioning
confidence: 58%
See 2 more Smart Citations
“…MSP1p19 antigen used in this study [18] is strongly recognized by the sera of infected individuals, and IgG responses were shown to be significantly associated with delayed infection following drug cure [19], and with clinical protection [20]. Our data show that, in both study groups, patients with cerebral malaria had significantly lower levels of anti-GPI antibodies compared to individuals with mild or asymptomatic malaria.…”
Section: Differential Antibody Responses To P Falciparum Glycosylphomentioning
confidence: 58%
“…Microtiter plates were coated with 100 µl per well of MSP1p19 at a concentration of 0.5 µg/ml. Plasma samples were diluted 1:100 in PBS with 1% BSA /0.05% Tween 20, and ELISAs were performed as described previously [9,19,24]. 7 The results are expressed as OD ratios, i.e., OD sample /OD negative control .…”
Section: Antigens and Elisa Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies, including this one, have observed a role for naturally acquired pre-erythrocytic antibodies [12,13] and naturally acquired cell-mediated immune responses [29] in preventing P. falciparum infection, although this association has not been observed in all studies [30]. On the other hand, some studies have concluded that pre-erythrocytic antibodies simply act as markers of exposure [31,32], with protection from infection being mediated by correlated blood-stage immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…A field study in Senegal in which factors such as reappearance of parasites, asymptomatic carriage of parasites, time to first clinical episode, and incidence of clinical episodes were considered led to the observation that antibodies to NANP, MSP-1p19, PfEMP-3, PfEB200 were associated with a lower risk for severe disease (Perraut et al, 2003). Another comprehensive study conducted in Senegal (305 children followed over 1 year) showed that different mechanisms mediate protection: higher levels of IgG1 specific for GLURP and IgG3 for MSP-2 in children correlate with resistance to malaria and high-level parasitemia compared to malaria-susceptible children (Courtin et al, 2009).…”
Section: Multi-antigen Responses: Reducing the Risk For Clinical Infementioning
confidence: 99%